Insight to changing morphologic patterns of glomerulopathy in adult Pakistani patients: an institutional perspective - Hashmi, Atif Ali (BMC Res Notes, 2016)
BACKGROUND: Idiopathic nephrotic syndrome encompasses diverse histogenetic patterns and depicts socioeconomic and demographic differences attributable to genetic profile, environmental factors and prevalence of infectious diseases. A lack of renal registry in our country necessitates a need to document changing histologic patterns of nephrotic syndrome as noted in different parts of the world. METHODS: We retrospectively analyzed 140 patients who underwent renal biopsy at Liaquat National Hospital from January 2009 to December 2013 over a period of 3 years. On the basis of clinical profile cases were segregated into nephritic and nephrotic syndrome and histologic and immunoflourescence findings were analyzed. RESULTS: Among 140 cases of glomerulonephritis diagnosed in the study period, 98 cases (70 %) were those of primary glomerulonephritis and 42 were of secondary glomerulopathy (30 %). Membranous glomerulonephritis was the most common primary glomerulonephritis (33.6 %) followed by focal segmental glomerulosclerosis FSGS (20.4 %), whereas lupus nephritis is the most common secondary glomerulopathy (47.6 %) followed by amyloidosis and diabetic glomerulosclerosis (16.6 % each). CONCLUSION: We found a considerable high incidence of membranous glomerulonephritis and FSGS in our population that entails a need to investigate prevalence of associated factors like Hepatitis B and HIV infections in population at risk. Moreover, renal biopsy registry would be instrumental in this regard to record changing disease pattern in this part of the world.